Proximal and extended aortic arch replacement in acute DeBakey type I aortic dissection - Narita, Masahiko; Tsutsui, Masahiro; Ushioda, Ryouhei; Kikuchi, Yuta; Shirasaka, Tomonori; Ishikawa, Natsuya; Kamiya, Hiroyuki (Frontiers in Surgery, 2023)
ABSTRACT Objective: This study aimed to compare the short- and long-term outcomes of proximal repair versus extensive arch surgery for acute DeBakey type I aortic dissection. Subjects: From April 2014 to September 2020, 121 consecutive patients with acute type A dissection were surgically treated at our institute. Of these patients, 92 had dissections extending beyond the ascending aorta. Methods: Of the 92 patients, 58 underwent proximal repair, including aortic root and/or hemiarch replacement, and 34 underwent extended repair, including partial and total arch replacement. Perioperative variables and early and late postoperative results were statistically analyzed. Results: The duration of surgery, cardiopulmonary bypass, and circulatory arrest was significantly shorter in the proximal repair group (p < 0.01). The overall operative mortality rate was 10.3% in the proximal repair group and 14.7% in the extended repair group (p = 0.379). The mean follow-up period was 31.1±26.7 months in the proximal repair group and 35.3±26.8 months in the extended repair group. During follow-up, the cumulative survival and freedom from reintervention rates at 5 years were 66.4% and 92.9% in the proximal repair group, and 76.1% and 72.6% in the extended repair group, respectively (p = 0.515 and p = 0.134). Conclusions: No significant differences were found in the rates of long-term cumulative survival and freedom from aortic reintervention between the two surgical strategies. These findings suggest limited aortic resection achieves acceptable patient outcomes.